2020
DOI: 10.1093/mnras/staa274
|View full text |Cite
|
Sign up to set email alerts
|

The better half – asymmetric star formation due to ram pressure in the EAGLE simulations

Abstract: We use the EAGLE simulations to study the effects of the intra-cluster medium (ICM) on the spatially resolved star-formation activity in galaxies. We study three cases of galaxy asymmetry dividing each galaxy in two halves using the plane (i) perpendicular to the velocity direction, differentiating the galaxy part approaching to the cluster center, hereafter dubbed as the "leading half", and the opposite one "trailing half", (ii) perpendicular to the radial position of the satellite to the centre of the cluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 56 publications
11
39
1
Order By: Relevance
“…These galaxy spectral indices are consistent with flattening due to ionization losses (Basu et al 2015;Chyży et al 2018) in a high density ISM. This flattening is expected at the low frequencies that we probe in this work and becomes increasingly important in the highest density regions of the ISM (Basu et al 2015), which is also consistent with enhanced ISM densities in jellyfish galaxies due to compression from ram pressure (e.g., Schulz & Struck 2001;Bekki 2014;Troncoso-Iribarren et al 2020;Cramer et al 2021).…”
Section: Spectral Index Measurementssupporting
confidence: 84%
See 1 more Smart Citation
“…These galaxy spectral indices are consistent with flattening due to ionization losses (Basu et al 2015;Chyży et al 2018) in a high density ISM. This flattening is expected at the low frequencies that we probe in this work and becomes increasingly important in the highest density regions of the ISM (Basu et al 2015), which is also consistent with enhanced ISM densities in jellyfish galaxies due to compression from ram pressure (e.g., Schulz & Struck 2001;Bekki 2014;Troncoso-Iribarren et al 2020;Cramer et al 2021).…”
Section: Spectral Index Measurementssupporting
confidence: 84%
“…This suggests that Hα + [Nii] emission, and therefore star formation, is enhanced along the leading side of the jellyfish galaxies, consistent with gas compression induced by ram pressure along the galaxy-ICM interface. As alluded to in Section 3, such an effect has been predicted by simulations of RPS (e.g., Bekki 2014;Troncoso-Iribarren et al 2020) and been reported observationally for a limited number of galaxies experiencing ram pressure (e.g., Gavazzi et al 2001;Boselli et al 2021). Further work is required to test whether these leading-side star formation enhancements are commonplace for galaxies undergoing RPS, and the results reported here are a step in that direction.…”
Section: Hα + [Nii] Sources Relative To Tail Directionsupporting
confidence: 63%
“…This increase in the star formation activity is probably due to an increase of the molecular gas fraction made possible by the increase of the external pressure (Blitz & Rosolowsky 2006), as again observed in some massive jellyfish galaxies (Moretti et al 2020b) and predicted by hydrodynamic simulations (Henderson & Bekki 2016;Troncoso-Iribarren et al 2020). NGC 4569 is significantly more massive than the dwarf IC 3476 and is thus able to retain the gas from external perturbations because of its deep potential well.…”
Section: The Galaxymentioning
confidence: 62%
“…Not only can RPS quench star formation by removing galaxy gas reserves, but simulations also predict a brief enhancement in star formation, prior to gas removal, due to compression in the ISM through the galaxy-ICM interaction (e.g. Steinhauser et al 2012;Ramos-Martínez et al 2018;Troncoso Iribarren et al 2020). This picture is supported by recent observations that have shown enhanced levels of star formation in galaxies thought to be undergoing RPS (Ebeling et al 2014;Poggianti et al 2016;Vulcani et al 2018;Roberts & Parker 2020).…”
Section: Jellyfish Galaxy Star Formationmentioning
confidence: 65%